Exercise training improves fasting glucose control - Lewis N; Norton K; Norton L (Dove Medical Press, 2012)
Lynda Norton,1 Kevin Norton,2 Nicole Lewis21School of Medicine, Flinders University, Adelaide, Australia; 2School of Health Science, University of South Australia, Adelaide, AustraliaPurpose: Numerous studies have measured changes in fasting blood glucose (FBG) levels in response to physical activity (PA) interventions. While studies involving clinical populations such as type 2 diabetics typically report significant reductions, most others report no change in FBG. This study investigated changes in FBG in apparently healthy adults following a PA intervention.Methods: We measured fingertip samples for FBG pre and post a 40-day PA program in 575 insufficiently active adults. The PA goal was at least 30 minutes of moderate exercise daily, and there was 73% compliance.Results: A PA questionnaire showed the average level of activity was 69 ± 46 min/wk preintervention, and this increased to 635 ± 458 min/wk postintervention. When the change in FBG was regressed against baseline FBG levels, there was a significant negative relationship (y = 2.623 – 0.471 × x; r = 0.472; P < 0.0001). The regression line showed, on average, subjects with low pre-study glucose levels had increased FBG while those with high levels had reductions in FBG.Conclusion: It appears that the body's response to PA training is to upregulate glucose control, which is reflected in tighter FBG levels around a physiological set point (5.6 mmol/L, in the present study). Regulation of blood glucose is a complex neuroendocrine process with numerous organs involved, but it was not possible in the present study to determine which of these regulatory steps are involved in exercise-induced changes of FBG.Keywords: physical activity, glucagon, insulin sensitivity